Are We Ready to Pilot a New Test Format for English Language Matura Exam? - Thaçi, Mimoza Berisha (European Journal of Multidisciplinary Studies, 2017)
Much of the debate about school improvement and raising of educational standards in Albania revolves around the issue of providing external standard tests which cannot allow students to be discriminated but allowed to receive equal opportunity to be assessed professionally in varying areas of English language. Being part of the National Agency of Exams, and part of standard testing service staff, it is obvious that taking the new challenges that education system is facing in consideration would be indispensable. The questions discussed are: What is to be changed; Based on what; What new features should the State Matura Exams (the foreign languages exams) have in Albania; Are the teachers and students prepared for this? This research paper will be focused on answering such questions and giving a clearer view on what has happened and what will happen with Matura Exams in Albania, especially with English Language Test. The aim of this paper is to see whatever has been applied and will be applied in future in State Matura Exams (external national standard assessment) based on concrete evidence.
Keywords: Albania Pilot New Test Format English Language Matura Exam